2
$\begingroup$

The real root of the equation $8x^3-3x^2-3x-1=0$ can be written in the form $\frac{\sqrt[3]{a}+\sqrt[3]{b}+1}{c}$, where $a$, $b$, and $c$ are positive integers. Find $a+b+c$.

I noticed that there was a $3x^2-3x-1$ present and I decided to add $(x+1)^3$ to get rid of this. When I did this, I ended up with $x=1/(9^{1/3}-1)$. I am not sure how to rationalize this crazy mess.

$\endgroup$
  • 3
    $\begingroup$ Multiply both the numerator and the denominator by $\sqrt[3]{81} + \sqrt[3]9 + 1$ and you will get... Hey indeed you are almost there ;) $\endgroup$ – Hw Chu May 31 '18 at 0:28
  • $\begingroup$ How did you know to multiply the denominator by that? $\endgroup$ – Dude156 May 31 '18 at 0:30
  • 1
    $\begingroup$ The formula $a^3 \pm b^3 = (a \pm b)(a^2 \mp ab + b^2)$. $\endgroup$ – Hw Chu May 31 '18 at 0:30
  • $\begingroup$ But this is not a cube, it is 1/3 power. How can we apply sum of cubes? Thanks for the help btw $\endgroup$ – Dude156 May 31 '18 at 0:31
  • 1
    $\begingroup$ Oh, as $9 - 1 = \sqrt[3]9^3 - 1^3$, you will get a cube implicitly somewhere. $\endgroup$ – Hw Chu May 31 '18 at 0:32
1
$\begingroup$

What I will do for most cubic equations:

Step 1:

If the equation $ax^3+bx^2+cx+d=0$ has $b=0$ then skip this step. Otherwise, let $y=x+\dfrac{b}{3a}$.

In this case:

$$8x^3-3x^2-3x-1=0$$

Let $y=x+\dfrac{b}{3a}=x-\dfrac{1}{8}\Rightarrow x=y+\dfrac{1}{8}$.

\begin{equation}\begin{aligned} 8x^3-3x^2-3x-1=0 &\Leftrightarrow 8\left(y+\dfrac{1}{8}\right)^3-3\left(y+\dfrac{1}{8}\right)^2-3\left(y+\dfrac{1}{8}\right)-1=0 \\ &\Leftrightarrow 8\left(y^3+\dfrac{3}{8}y^2+\dfrac{3}{64}y+\dfrac{1}{512}\right) -3\left(y^2+\dfrac{1}{4}y+\dfrac{1}{64}\right)-3y-\dfrac{3}{8}-1=0\\ &\Leftrightarrow 8y^3-\dfrac{27}{8}y-\dfrac{45}{32}=0\\ \end{aligned}\end{equation}

The last equation now has $b=0$.

Step 2:

After having the last equation in the form $ax^3+cx+d=0$, write it again as $x^3+\dfrac{c}{a}x+\dfrac{d}{a}=0$ (if $a\ne 1$) and find real numbers $z,t$ that satisfy ${\begin{cases}z^3+t^3=\dfrac{d}{a}\\zt=\dfrac{-c}{3a}\end{cases}}$

This is why:

$8y^3-\dfrac{27}{8}y-\dfrac{45}{32}=0$

$\Leftrightarrow y^3-\dfrac{27}{64}y-\dfrac{45}{256}=0$

If you can find $z,t\in\mathbb{R}$ so that ${\begin{cases}z^3+t^3=\dfrac{-45}{256}\\zt=\dfrac{27}{192}\end{cases}}\Leftrightarrow {\begin{cases}z^3+t^3=\dfrac{-45}{256}\\z^3t^3=\dfrac{729}{262144}\end{cases}}\Leftrightarrow {\begin{cases}z=\sqrt[3]{\dfrac{-81}{512}}\\t=\sqrt[3]{\dfrac{-9}{512}}\end{cases}}\Leftrightarrow {\begin{cases}z=\dfrac{\sqrt[3]{-81}}{8}\\t=\dfrac{\sqrt[3]{-9}}{8}\end{cases}}$ then

$y^3-3yzt+z^3+t^3=0$

$\Leftrightarrow (y+z+t)(y^2+z^2+t^2-yz-zt-ty)=0$

$\Leftrightarrow (y+z+t)2(y^2+z^2+t^2-yz-zt-ty)=0$

$\Leftrightarrow (y+z+t)((y-z)^2+(z-t)^2+(t-y)^2)=0$

$\Leftrightarrow y=-z-t$ because you will find that $z\ne t$.

$\Rightarrow x=\dfrac{1}{8}-z-t=\dfrac{1}{8}-\dfrac{\sqrt[3]{-81}}{8}-\dfrac{\sqrt[3]{-9}}{8}=\dfrac{-\sqrt[3]{-81}-\sqrt[3]{-9}+1}{8}=\dfrac{\sqrt[3]{81}+\sqrt[3]{9}+1}{8}.$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.